The process of design thesis in landscape architecture - Abdul Malek, Nurhayati (IIUM Press, 2014)
Landscape Architecture is the intertwining aspects of natural sciences, arts, economics, and culture. It is a profession that helps design a ‘place’ that connects land and human, which has many applications, from a small scale design project to a more significant and large scale urban design as well as regional planning projects. Landscape Architect is indeed the person who designs outdoor environments.